A study of fetomaternal outcome of hepatic disorders in pregnancy - Jain, Mahima; Thaker, Himani (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Liver is a vital organ to maintain physiology of the body and supports every organ of the body. Its proper functioning during pregnancy is essential for a good maternal and fetal outcome. The study analyses the causes and fetomaternal outcome in pregnancies with jaundice and suggests measures to reduce morbidity and mortality. Methods: This is a one-year prospective study in a tertiary care institute during which 7165 deliveries are conducted. Total 55 cases of Jaundice with pregnancy are identified and studied for clinical, biochemical profile, etiology and maternal and fetal outcome. 8 maternal deaths are reported amongst this study group. Results: In this study 55 cases of hepatic disorders in pregnancy are studied. The age group reported is 21-29 years. Majority 72% cases belong to rural areas and 85% in lower socioeconomic class. 96.3% patients were in the third trimester of pregnancy. Most common etiology of hepatic disorders in pregnancy is acute viral hepatitis followed by intrahepatic cholestasis of pregnancy and preeclampsia and HELLP syndrome. In acute viral hepatitis 81% patients were hepatitis E positive. Most common complication are DIC followed by hemorrhagic shock and subsequently AKI and septicemia. 77.7% babies were born alive and 30.9% NICU admission due to severe birth asphyxia and prematurity. Of these 16.6% died in neonatal period. Maternal mortality in 14.5% patients due to viral hepatits, HELLP and septicemia. Conclusions: Jaundice in pregnancy is a rare medical disorder and deadly combination affecting maternal and fetal outcome. Earl detection and timely intervention with multidisciplinary approach including obstetrician, neonatologist, intensivist and skilled nursing care can help to reduce maternal mortality and morbidity.